flows - Grigoryeva , Elena (project baikal, 2025)
The topic of FLOWS is perhaps one of the favourite topics in our journal, and we were pleased to return to it at the next stage of PB’s development in its third decade.The whole variety of approaches and methods for analysing reality can be seen as a combination of two opposing paths. Object-based approaches focus on objects: people, buildings, cities, regions. Process approaches see the picture of the world as an intertwining of trajectories along which a variety of entities – people, money, goods, armies, ideas... – move.What does the development of Irkutsk look like through the prism of flows? What is the fate of the stream projects of Irkutsk sixtiers and their followers – ‘Green Diameter’, ‘Baikal Ray’, 130 Quarter? The NER project of Ilya Lezhava and Alexei Gutnov, having survived the period of worldwide fame, has mostly remained on paper. Do Irkutsk projects have any chances for implementation?Apart from our favourite Irkutsk, the heroes of this issue are Krasnoyarsk, Khabarovsk, Suzdal, the stations of Transsib, BAM and CER, and ancient cities of the Eastern Mediterranean. This issue is a meeting place of authors from different disciplines: urban planners and architects, sociologists and historians, psychologists, theorists and practitioners....The issue opens with international and Russian architectural events and Siberian festivals – ARCHIGESH and ARCHBUKHTA.
Keywords: flows; object-based approaches; process approaches